Rights from wrongs: an educational unit on patient rights for students - Lakoski, Samantha, author; Jeckel, Kimberly, advisor; Robinson, Gina, committee member (Colorado State University. Libraries, 2025)
Patient rights lie at the intersection of two of the most daunting systems for everyday people, the medical and legal systems. Already stressful situations can become more confusing when a person doesn't know what protections they are entitled to as they enter a healthcare setting. Lack of awareness can be traced back to the lack of a comprehensive patient rights document in the United States. Rather, patient rights are distributed over various pieces of federal legislation, state legislation, and court cases. This paper outlines an educational unit for high school students that aims to define patient rights, outline key pieces of legislation, highlight population considerations, and identify significant legislation specific to Colorado. The goal of this unit is to help students become more familiar with the protections they are afforded in a medical setting, so they can feel more empowered when interacting with medical professionals. Through this empowerment, students will feel more comfortable seeking necessary medical help, communicating with medical professionals, and advocating for themselves if the need arises.
Keywords: Honors Thesis